An improved method with a wider applicability to isolate plant mitochondria for mtDNA extraction. Issue 1 (December 2015) - Ahmed, Zaheer; Fu, Yong-Bi
Abstract Background Mitochondria perform a principal role in eukaryotic cells. Mutations in mtDNA can cause mitochondrial dysfunction and are frequently associated with various abnormalities during plant development. Extraction of plant mitochondria and mtDNA is the basic requirement for the characterization of mtDNA mutations and other molecular studies. However, currently available methods for mitochondria isolation are either tissue specific or species specific. Extracted mtDNA may contain substantial chloroplast DNA (cpDNA) and nuclear DNA (nDNA) and its end use efficiency can be reduced. Clearly, an effective mitochondria isolation method is warranted with wider applicability and with minimum contamination from cpDNA and nDNA. Results Here we reported an improved method for isolating mitochondria from dry wheat seeds and its extension to dead seeds, viable seeds, etiolated leaf tissue and several other plant species: oat, Arabidopsis, flax, and yellow mustard. The isolated mitochondria were successfully used to extract mtDNA with QIAamp DNA mini kit (Qiagen). The extracted mtDNA from the assayed samples of these species was intact in large quantity and showed little contamination from nDNA, cpDNA, RNA, and proteins. The mtDNA extracted from dead wheat seeds was also substantial, but more degraded and less intact when compared to those from viable seeds and other tissues. Conclusion The improved method was successfully applied to isolate mitochondria and extract mtDNA from several different tissues and plant species. The major advance in the improvement lies in its wider application with the same mitochondria extraction medium to different tissues and species. The improvement is significant, as it helps to widen the scope of future plant mitochondria research.